MENTAL BULLYING AND ITS IMPACT TO VICTORIA DAWSON IN DANIELLE STEEL’S BIG GIRL - KARINA RACHMAWATI (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2014)
MENTAL BULLYING AND ITS IMPACT TO VICTORIA DAWSON IN DANIELLE STEEL’S BIG GIRL Karina Rachmawati English Literature, Faculty of Languages and Arts, Surabaya State University rahmakarina92@gmail.com Prof. Dr. FD Kurnia, M.Pd. English Department, Faculty of Languages and Arts, Surabaya State University Abstrak Novel Big Girl adalah novel Danielle Steel yang mempunyai tema Mental Bullying dalam penulisannya. Victoria Dawson mental bullying menjadi topic utama dalam penelitian ini. Dengan demikian penelitian ini berfokus pada tiga masalah utama (1) Mental Bullying seperti apa yang dialami oleh Victoria Dawson dalam novel Big Girl oleh Danielle Steel (2) Penyebab Victoria Dawson Mental Bullying dalam novel Big Girl oleh Danielle Steel (3) Dampak Victoria Dawson Mental Bullying dalam novel Big Girl oleh Danielle Steel. Data dari tesis ini diambil dari novel sebagai sumber utama dan membaca intensif untuk langkah analisis berikutnya. Untuk menjawab semua masalah, penelitian ini menggunakan teori Psychology of Bullying untuk menggambarkan Mental Bullying, Penyebab dan Dampaknya. Penelitian kepustakaan digunakan untuk data yang dibutuhkan perguruan tinggi. analisis yang digunakan untuk menganalisis data yang dikumpulkan berdasarkan teori. Deskripsi digunakan untuk menjelaskan hasil analisis. Setelah melalui analisis yang panjang dengan menggunakan tiga macam metode di atas,Ditemukan bahwa mental bullying membawa dampak buruk bagi korban bullying karena menggunakan kata kata dan emosi untuk menghina seseorang. Korban mental bullying mengalami depresi, merasa takut, dan merasa kesepian untuk bergaul dengan orang lain dan sebagian besar dari mereka tidak mempunyai teman. Kata kunci: Bullying, Mental Bullying, Insult Abstract Big Girl is Danielle steel’s novel which has Mental Bullying themes she writes on throughout her work. Victoria Dawson mental bullying has become the main topic of this study. Thus this study focuses on three major problems, (1) What mental bullying is experienced by Victoria Dawson in Danielle Steel’s Big Girl, (2) What are the causes of Victoria Dawson mental bullying in Danielle Steel’s Big Girl, and (3) What are the impacts of Victoria Dawson mental bullying in Danielle Steel’s Big Girl. The data of the thesis is taken from the novel as the main source and intensive reading to next step of analysis. To answer the all problems, this study is using Psychology of Bullying Theory to depict the mental bullying, causes and impacts. This study also used library research, analysis and description. Library research is used to college data needed. An analysis is used to analyze the collected data based on the theories. Description is used to describe the result of analysis. After getting through long analysis by using three kinds of method above, it finds out that mental bullying bring bad impacts to victim of bullying because using words and emotions to insult someone. The mental victims of bullying are depressed, always feeling afraid and feel lonely to associate with other people and most of them has not a friend. Key words: Bullying, Mental Bullying, Insult. INTRODUCTION Many people may probably had problems. One of their problems related with psychological. Psychology term is a thing that can not be separated far from human life. Psychology terms have touched all of the aspect about human life. Everything about human life’s conflict has always touched the deepest side of human’s psychology condition. There must be something that related to the psychology. When somebody gets the hurt from anything, there is always a big possibility of one who get the messy thing in his mind; it could influence his internal condition such as his way of thinking, his emotional reaction, etc. For the most serious effect, they might get the trauma and also the death of somebody because they can not control the internal conflict inside their soul. One of psychological experiences in this paper is Bullying. Bullying is a serious issue that is faced by many people, and can leave a people to live in complete fear. Bullying it self mean typically a form of repeated, persistent and aggressive behaviour directed at an individual or individuals that is intended to cause (or should be known to cause) fear and distress and/or harm to another person’s body, feelings, self-esteem or reputation. Bullying occurs in a context where there is a real or perceived power imbalance. Bullying is the use of force to intimidate someone. It can happen to anyone, anywhere and any time. It can come from a single person or a group. Bullying can be delivered verbally or in some extreme cases physically where the victim suffers actual bodily harm. Bullying behavior can be direct or indirect bullying. Direct bullying behaviors (overt) involve behaviors that are observable and that are usually expressed by physical and verbal means. Usually direct bullying involves relatively open attacks on a victim and are “in front of your face” behaviors. However, bullying behavior is not always hitting, kicking, teasing, or name calling. Children who bully others may use subversive acts that hurt just as much, but are harder to detect. Indirect bullying is related with Mental Bullying. This bullying practice occurs secretly and in the outside of our monitoring radar. Examples of indirect bullying are leaving others out on purpose, spreading rumours to destroy another’s reputation or getting others to dislike another person, a cynical viewing, public humiliating, isolating, humiliating, accusing, gossiping, slandering, snapping, glaring and pouting.. This is covert bullying or “behind your face” behaviours. Bullying is not just a childhood problem: it extends to adulthood, the boardroom, shop floor and the dysfunctional family. (Beane, 2003:6). It can be concluded that bullying related with mental abuse, also known as mental bullying. Mental Bullying can occur in close relationships, including parent/child relationships, marital relationships or sibling relationships. Mental bullying causes damage in the victim as she is made to believe she is worthless and at fault. Mental bullying is particularly harmful on children because of the impact it has on developing self-esteem and patterns relating to others. As mentioned above, one of the novels deals with theme Mental Bullying is Big Girl, because this study will describe about Victoria Dawson mental bullying is the main topic of Big Girl, because it’s interesting for discussed through topic. Victoria Dawson experienced mental bullying when the firstborn child, she grows up out of place in her family because of her fair hair and thicker build. While the rest of her family is dark haired and thin, Victoria is blond, blue-eyed and according to her father, has his grandmother’s ‘big’ build. Victoria puts up with her father’s thinly-veiled barbs while her mother constantly drops weight remarks. Meanwhile her parents dote on the younger sister Grace, as she is beautiful and thin. In accordance of background study above, it can be simplify to discuss among three problems that emerge as significant concern toward this novel. 1. What mental bullying is experienced by Victoria Dawson in Danielle Steel’s Big Girl? 2. What are the causes of Victoria Dawson mental bullying in Danielle Steel’s Big Girl? 3. What are the impacts of Victoria Dawson mental bullying in Danielle Steel’s Big Girl? This study will uses Psychology of Bullying theory in order to answer the question in the statement of the problems, this study tries applying theory as the base of analysis this theory is: Psychology of bullying to analyze about Victoria Dawson Mental Bullying in Danielle Steel’s Big Girl. The first problem is what mental bullying is experienced by Victoria Dawson in Danielle Steel’s Big Girl. This statement will use Psychology of bullying theory. with several kinds of mental bullying are; public humiliating, isolating, accusing, gossiping, slandering, snapping, embarrassed, humiliated and condescended. But of the several kinds mental bullying that have been mentioned above, which includes kinds of mental bullying that occurred and depicted to Victoria mental bullying are humiliation; embarrassed and condescended. Then the second is what are the causes of Victoria Dawson mental bullying in Danielle Steel’s Big Girl. This statement will use Psychology of Bullying theory. The causes of Victoria Dawson mental bullying its come from Family factor, There are two causes that made Victoria experienced Mental Bullying from family factor; Narcissistic her parents and Being Different from her Family. And the last is What are the impacts of Victoria Dawson mental bullying in Danielle Steel’s Big Girl. This statement will use Psychology of Bullying theory. The impacts of Victoria Dawson mental bullying its she feel sadness and self esteem which is there are three impacts because of Victoria feel sadness and self esteem; Search for Self Identity to New York, Struggle from her Body Image, and See a Psychiatrist. RESEARCH METHOD This thesis is regarded as a descriptive-qualitative study and use a library research. Therefore, the data will not be in number. The descriptive method of his study can be elaborated as follows. The main source of the study is taking from Danielle steel novel entitled Big Girl by Danielle steel, is an American novelist who is currently the bestselling author alive and the fourth bestselling author of all time, with over 800 million copies sold. Based in California for most of her career, Steel has produced several books a year, often juggling up to five projects at once, all her novels have been bestsellers, including those issued in hardback. Big Girl published by Delacorte Press on February 23, 2010. In analyzing the data, a descriptive qualitative method was applied. The data mostly got from library research. The data consist of the main data and additional data. The main data are collected or taken from Danielle Steel’s Big Girl in the form of quotations, comments on the events and action related with the issue that is Victoria Dawson mental bullying, the causes and the Impacts of Victoria Dawson mental bullying in Big Girl. The supporting data are taking from many sources such as articles, reference books, journals, magazines, internet sources that are relevant with the topic and other related sources. Then the data are collected, clarified, analyzed and made a conclusion. To assist and strengthen the data will be analyze; Victoria Dawson mental bullying in Danielle Steel’s Big Girl used Psychology of bullying, the causes and the impacts of Victoria Dawson mental bullying. Overall, those concepts are relating with the Victoria characterization in her life. This study contains four chapters. The first chapter is about introduction consist of background of the study, statement of the problem, purpose of the study, significance of the study, limitation of the study, research method and organization of the study. The second chapter is Review related of literature; consist of Psychology of bullying, Victoria Dawson mental bullying, the causes and the impacts of Victoria Dawson mental bullying, and paradigm of analysis. The third chapter is analysis about the novel Big Girl. The fourth or the last chapter in this study is conclusion of the analysis. This study encloses appendices: the biography of Danielle Steel and the synopsis of Big Girl. ANALYSIS Which the theories that are state in the previous chapter are used as a guide to accomplish it. This analysis will divided into several sub chapters. The first part in this chapter is about the Mental Bullying is experienced by Victoria Dawson in Danielle Steel’s “Big Girl”. The second part is about the causes of Victoria Dawson mental bullying and the last chapter about the impacts of Victoria Dawson mental bullying in the novel. Victoria Dawson Mental Bullying Bullying is emotional negative action performed against others who have traits that differ from other large groups, for example, of different races, shapes hair, skin color and so on. Bullying can be emotional done by cursing or acting intentionally using motion - a particular movement aimed to insult. (Elliot , 2005:2). One of kind bullying is related with mental abuse, and usually called with mental bullying. According to Sejiwa, (2007:2) mental bullying is a type of bullying. It is one of the most hurtful types of bullying. It is the act of using words and emotions to hurt someone. Mental bullying has two types, Verbal and Emotional. In this part it will discuss about Victoria Dawson mental bullying. To depict Victoria mental bullying, it uses Psychology of Bullying theory, with several kinds of mental bullying are; public humiliating, isolating, accusing, gossiping, slandering, snapping, embarrassed, humiliated and condescended. But of the several kinds mental bullying that have been mentioned above, which includes kinds of mental bullying that occurred and depicted to Victoria mental bullying are: Humiliation Humiliation is a kind of mental bullying that depicted to Victoria Dawson mental bullying. Big Girl tells about Victoria Dawson as the main character, she experienced mental bullying from her parents and people around her because different physical appearance than her family. Victoria parents were born from perfect physical appearance. Her father, mother and sister have the same appearance, but Victoria was different. When Victoria was a child, she experienced mental bullying from people around her and especially from her parents. In Victoria Dawson mental bullying is found quotations to depicted humiliation as kind of mental bullying. Victoria Dawson is an outcast in her own family, the round peg in a family of square holes. It is precisely her roundness that marks her as an outsider. Chubby, blond and blue-eyed in a family of slim, dark stunners, she is the daughter whom her father called